Evaluation of a health service adopting proactive approach to reduce high risk of lung cancer: The Liverpool Healthy Lung Programme. (August 2019) - Ghimire, Bhagabati; Maroni, Roberta; Vulkan, Daniel; Shah, Zoheb; Gaynor, Edward; Timoney, Michelle; Jones, Lisa; Arvanitis, Rachel; Ledson, Martin; Lukehirst, Linda; Rutherford, Paul; Clarke, Faye; et al.
Highlights: This community-based early diagnosis programme is reaching a deprived population. The programme detected lung cancers at an early stage, 76% at stage I or II. The earlier detection implied a projected 22% decrease in risk of death from lung cancer. Abstract: Objectives: This Liverpool Healthy Lung Programme is a response to high rates of lung cancer and respiratory diseases locally and aims to diagnose lung cancer at an earlier stage by proactive approach to those at high risk of lung cancer. The objective of this study is to evaluate the programme in terms of its likely effect on mortality from lung cancer and its delivery to deprived populations. Methods: Persons aged 58–75 years, with a history of smoking or a diagnosis of chronic obstructive pulmonary disease (COPD) 2 according to general practice records were invited for lung health check in a community health hub setting. A detailed risk assessment and spirometry were performed in eligible patients. Those with a 5% or greater five-year risk of lung cancer were referred for a low dose CT 3 scan. Results: A total of 4 566 subjects attended the appointment for risk assessment and 3 591 (79%) consented to data sharing. More than 80% of the patients were in the most deprived quintile of the index of multiple deprivation. Of those attending, 63% underwent spirometry and 43% were recommended for a CT scan. A total of 25 cancers were diagnosed, of which 16 (64%) were stage I. Comparison with the national stage distribution implied that the programme was reducing lung cancer mortality by 22%. Conclusions: Community based proactive approaches to early diagnosis of lung cancer in health deprived regions are likely to be effective in early detection of lung cancer.